Glycine Cleavage System and cAMP Receptor Protein Co-Regulate CRISPR/cas3 Expression to Resist Bacteriophage - Yang, Denghui (Viruses, 2020)
The CRISPR/Cas system protects bacteria against bacteriophage and plasmids through a sophisticated mechanism where cas operon plays a crucial role consisting of cse1 and cas3. However, comprehensive studies on the regulation of cas3 operon of the Type I-E CRISPR/Cas system are scarce. Herein, we investigated the regulation of cas3 in Escherichia coli. The mutation in gcvP or crp reduced the CRISPR/Cas system interference ability and increased bacterial susceptibility to phage, when the casA operon of the CRISPR/Cas system was activated. The silence of the glycine cleavage system (GCS) encoded by gcvTHP operon reduced cas3 expression. Adding N(5), N(10)-methylene tetrahydrofolate (N(5), N(10)-mTHF), which is the product of GCS-catalyzed glycine, was able to activate cas3 expression. In addition, a cAMP receptor protein (CRP) encoded by crp activated cas3 expression via binding to the cas3 promoter in response to cAMP concentration. Since N(5), N(10)-mTHF provides one-carbon unit for purine, we assumed GCS regulates cas3 through associating with CRP. It was evident that the mutation of gcvP failed to further reduce the cas3 expression with the crp deletion. These results illustrated a novel regulatory pathway which GCS and CRP co-regulate cas3 of the CRISPR/Cas system and contribute to the defence against invasive genetic elements, where CRP is indispensable for GCS regulation of cas3 expression.